Pembinaan Integrasi Sekolah Dasar Dan Madrasah Diniyah Takmilyah (MDT) Di Kota Jambi - Wulandari, Tati; Novanda, Ramazani (LOKOMOTIF ABDIMAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
This activity aims to reveal how the regulations regarding the integration of Diniyah Takmiliyah Elementary Schools and Madrasahs are, find strategies that can be implemented to realize these regulations, and formulate possible efforts to ensure that the integration of Diniyah Takmiliyah Elementary Schools and Madrasahs in Jambi City is carried out smoothly. The integration development activities for Diniyah Takmiliyah Primary Schools and Madrasahs are carried out in 3 stages. The first stage is the stage of determining activity objectives, the second stage is the activity planning stage and the third stage is the activity implementation stage. Fostering the integration of Primary Schools and MDT is the first step in efforts to clarify existing integration regulations. This activity also opens communication between the Jambi City Ministry of Religion and the Jambi City Education Office in implementing educational policies involving both parties, for example in the implementation of religious education. This activity also revealed several problems faced by elementary schools and MDTs in implementing religious education. This activity is limited to the preparation and formulation of regulations based on analysis of problems found during the activity. The plan to formulate a policy text regarding the integration of Schools and MDT will be carried out as soon as possible as a follow-up step to this activity. This activity contributes to schools and MDT so that they can integrate well in carrying out the religious education process. This activity was also carried out to find strategies that could be used as an effort to form regulations regarding school integration with MDT in the city of Jambi.